(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: P. aeruginosa is one of the most common causes of infection in burns and wounds and it is the major cause of death in burn patients. This organism is frequently feared because it causes severe hospital-acquired infections, especially in immunocompromised hosts, and is often antibiotic resistant; complicating the choice of therapy. Thus, there is continuous need for enhancing the antibacterial efficacy of antibiotics against P aeroginosa. Objective:This study was conducted to determine the MIC of antibiotics used in combination for resistant isolates of Pseudomonas aeruginosa and measure the effect of EDTA in increasing the inhibition effect of these antibiotics. Methods: P. aeruginosa was identified microscopically and biochemically. The swab samples from burns and wounds were collected from patients of AL-YarmooK, Baghdad and Al-Kadhimiya Teaching Hospitals. Minimum inhibitory concentration (MIC) was used to evaluate antibiotics effectiveness, while fractional inhibitory concentration (FIC) was used to evaluate the effect of antibiotics combination on pathogenic bacteria (P.aeruginosa). Disk diffusion assay were used to determine the inhibition zone of antibiotic disk (with and without EDTA) against P. aeruginosa. Results:Ten isolates were selected according to their pattern of resistance as those showing multi-drug resistance and tested to specify their minimum inhibitory concentration for (amikacin, gentamicin, ceftazidime, and ciprofloxacin). Amikacin had the lowest MIC compared with others. Among combinations, the combination of ß-lactam antibiotics with amikacin was found to be the most effective combination. Results showed that EDTA increases the effect of antibiotic against P. aeruginosa isolates especially when it was combined with aminoglycoside antibiotics. Conclusion: Amikacin is the most effective agent against Pseudomonas aeruginosa especially when combined with ceftazidime, more over; EDTA increases the activity of antibiotic against pseudomonas aeruginosa especially when combined with aminoglycoside antibiotics. Keywords:P aeruginosa, minimum inhibitory concentration (MIC), Fractional inhibitory concentration (FIC), Ethylenediaminetetraactic acid (EDTA).